Syingir: Transformasi Puisi Arab ke dalam Puisi Jawa - . Hindun (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2012)
Syingir is a advice poem that uses the daily Javanese Language and sung individually or together. Syingir developed in pesantren [lslamic boarding school] or in Islamic region, in Central Java and East Java. The creators are kyai or da'i. This poem created to spread the teachings of Islam including akidah, syariah, and muamalah by means of an easy to remember so it was easy to be understood. In terms of firm, syingir closer to the pattern of traditional Arabic poem, syi'ir known as the pattern of al-Khalil. Usage that pattern was caused by penyingir are kiais that had been familiar with ilmul arudl wal-'-qafiyah, the science of rhythm and rhyme in Arabic poetry. While in the term of content, syingir as a religious message is the transformation of the contents of the Arabic poetry which is at-ta'lim (education).